2020
DOI: 10.1177/0956462420920136
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and correlates of HIV self-testing among university students in northern Nigeria

Abstract: Concerns about stigma and confidentiality limit the uptake of HIV testing and counseling (HTC) among young adults. HIV self-testing has been offered as a youth-friendly alternative to conventional HTC. We conducted a cross-sectional study to assess HTC uptake, willingness to self-test, and their predictors among university students ( n =  399) in Kano, Nigeria. Anonymous self-administered questionnaires were provided to participants. Adjusted odd ratios were generated for predictors with logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…In Nigeria, the country in West Africa worst affected by the COVID-19 pandemic (18), the concept of individuals having access to technologies for self-testing for infectious diseases is not new. The acceptability of HIV self-testing is high (19)(20)(21), although its use is not yet widespread, and so is the acceptability of malaria self-testing by the general public (22) and healthcare workers (23). Access to SARS-CoV-2 self-testing kits may help increase the prompt detection of infection in asymptomatic and mildly symptomatic cases and improve the currently low rate of COVID-19 testing in the country (24).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, the country in West Africa worst affected by the COVID-19 pandemic (18), the concept of individuals having access to technologies for self-testing for infectious diseases is not new. The acceptability of HIV self-testing is high (19)(20)(21), although its use is not yet widespread, and so is the acceptability of malaria self-testing by the general public (22) and healthcare workers (23). Access to SARS-CoV-2 self-testing kits may help increase the prompt detection of infection in asymptomatic and mildly symptomatic cases and improve the currently low rate of COVID-19 testing in the country (24).…”
Section: Introductionmentioning
confidence: 99%
“…We found that one-in-five female students had ever used HIVST, which is higher than the 9% reported among Nigerian university students [ 20 ]. Students from Uganda were assessed at least 2 years after those in Nigeria, and because HIVST is being scaled-up in sub-Saharan Africa, Ugandan students in this study may have had better access to HIVST.…”
Section: Discussionmentioning
confidence: 63%
“…Notably, HIV testing among female university students was below the national average for AGYW (92% for older AGYW) in Uganda [ 8 ]. HIVST can bridge the gaps in HIV testing because it is highly acceptable to AGYW [ 14 , 20 ]. Additionally, HIVST is crucial in reaching key populations and their partners, especially when access to health facilities is constrained, as was the case of COVID-19 lockdown [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…44,45 In a study by Iliyasu et al 2020, a higher uptake of HIV self-testing was observed compared to other testing strategies among university students in Nigeria. 46 Self-testing may avoid stigmatization, but positive results need to be linked to care.…”
Section: Discussionmentioning
confidence: 99%